Including Classical Galactosaemia in the Expanded Newborn Screening Panel Using Tandem Mass Spectrometry for Galactose-1-Phosphate - Arieh S. Cohen; Marta Baurek; Allan M. Lund; Morten Dunø; David M. Hougaard (MDPI AG, 2019)
Galactosaemia has been included in various newborn screening programs since 1963. Several methods are used for screening; however, the predominant methods used today are based on the determination of either galactose-1-phosphate uridyltransferase (GALT) activity or the concentration of total galactose. These methods cannot be multiplexed and therefore require one full punch per sample. Since the introduction of mass spectrometry in newborn screening, many diseases have been included in newborn screening programs. Here, we present a method for including classical galactosaemia in an expanded newborn screening panel based on the specific determination of galactose-1-phosphate by tandem mass spectrometry. The existing workflow only needs minor adjustments, and it can be run on the tandem mass spectrometers in routine use. Furthermore, compared to the currently used methods, this novel method has a superior screening performance, producing significantly fewer false positive results. We present data from 5500 routine newborn screening samples from the Danish Neonatal Screening Biobank. The cohort was enriched by including 14 confirmed galactosaemia positive samples and 10 samples positive for other metabolic disorders diagnosed through the Danish newborn screening program. All galactosaemia positive samples were identified by the method with no false positives. Furthermore, the screening performance for other metabolic disorders was unaffected.